Brucellosis: Penyakit Zoonosis yang Terabaikan - Risqa Novita (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2016)
Brucellosis is one of the diseases from animals to humans which draw serious attention by the government with regrad to high economic losses caused by a decline on the productivity of animals and humans. Indonesia has not been free from Brucellosis in animals, only several areas such as Riau, South Sumatra, Jambi, Riau Islands, West Sumatera, Bengkulu, Lampung, West Nusa Tenggara and Kalimantan Island were noted as free areas of Brucellosis until 2014. The Purpose of this review is to study Brucellosis as neglected zoonoses disease which has big potential to human diseases, mainly due to abortus in the first and second trimester of pregnancy. The prevalence of Brucellosis in Malaysia was 25%, where 75% of those cases caused abortion in women patients. Prevalence data of Brucellosis in human in Indonesia is still difficult to be obtained. Based on the research in 1995, founded antibody against Brucella in slaughterhouse and dairy farm workers in Jakarta was identified as 13.5%.